Cost competition, fragmentation and globalization - Michael C. Burda; Barbara Dluhosch (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
This paper proposes a model in which the removal of barriers to trade and factor mobility is associated with endogenous fragmentation of the value-added chain. Fragmentation is the outcome of cost competition - the profit-maximizing choice of cost structure by monopolistically competitive firms. An expansion of the integrated trading area can induce globalization not only in the horizontal dimension associated with love-of-variety preferences, but also vertically as firms vary specialization of production stages. While increased trade is likely to induce fragmentation when the number of firms is fixed, free entry can either reverse or intensify this result.
urn:nbn:de:kobv:11-10049826
Keywords: F10; L23; O33; 330; International Trade; Organization of Production; Technology Choice; Division of Labor